Mass Communication Tools: Exploring Effectiveness for Assam Tea Worker Community - Suresh Goduka (Journal of Advanced Research in Journalism & Mass Communication, 2024)
Assam's tea workers, a diverse mix of ethnic communities, have lived in isolated tea garden colonies since the British era. This research paper presents a field survey among these workers, assessing the effectiveness of various mass media tools in disseminating public awareness messages. The survey, comprising 15 questions, aimed to measure seven indicators related to the visibility and understanding of different media messages. The findings reveal a poor reach and impact of these mass media tools among the studied population.